Designing Context-Based Video Instruction in Enhancing the Conceptual Understanding of Grade XI Students - Russel T. Soltura (Universitas Pendidikan Ganesha, 2021)
This study generally aims to design context-based video instruction in accordance to TPACK framework in order to enhance the conceptual understanding of the students with regards to cell biology. The current study assessed the level of conceptual understanding of 73 Grade 11 student-respondents of Quezon Science High School in cell biology prior to the utilization of context-based video instruction. It sought to test the significant difference between the pretest and posttest scores in the said discipline. This study identified the level of acceptability of the context-based video instruction as perceived by the student-respondents in terms of learning objectives, accuracy, appeal, clarity, and usability. The respondents are enrolled in STEM strand of Senior High School, S.Y. 2020 – 2021. Questionnaires and the context-video instruction were developed and validated to assess and evaluate the research objectives of this study. The topics in cell biology obtained an overall MPS value of 31.15%. It means that the student-respondents have specific misconceptions about the different concepts in the said topic prior to the utilization of the said learning digital resources. The appropriateness of the language, general appearance of the teacher, quality of video, lighting, animation, and video transitions were some of the parameters considered in designing the video lectures. The overall t-value of 59.57 is greater than the tabular value of 1.99. It implies that the developed context-based video instruction in enhancing the conceptual understanding in cell biology is a valid tool in the teaching-learning process. Furthermore, the developed context-based video instruction in enhancing the conceptual understanding is commendable for use in terms of learning objectives, clarity, accuracy, appeal, and usability.